Phytochemical compounds and pharmacological activities of Ipomoea batatas L.: An updated review - Hendy Suhendy; Irda Fidrianny; Muhamad Insanu (Pensoft Publishers, 2023)
This article provides an overview of Ipomoea batatas L., the Ipomoea genus. The review covers traditional uses, nutritional value, phytochemical compounds, pharmacological activities, and toxicity studies. Data were collected from scientific databases and search engines. Sweet potatoes are used in various countries for traditional uses such as dietary fiber sources, treating allergies, and providing energy in diabetes mellitus treatment. The primary phytochemical compounds in Ipomoea batatas are phenolic compounds, flavonoids, anthocyanins, and carotenoids. Sweet potato contains several nutritional constituents: vitamin C, protein, fiber, carbohydrates, β-carotene, and minerals. Sweet potato exhibits various pharmacological activities, such as antioxidant, aphrodisiac, anticancer, and anti-inflammatory. The types of phytochemical compounds in each part of the plant are different. Each pharmacological activity and mechanism of action depends on the phytochemical compounds, part and variety of the plant, and extraction solvent. However, further study is required to investigate the chronic toxicity of Ipomoea batatas.